Problematika Pembelajaran Menulis Permulaan pada Siswa Sekolah Dasar - Salsabila, Kania; Wahyuni, Endang Sry; Arman, Diah Mulyani; Hoiriyah, Verny Nur (Lembaga Yasin AlSys, 2023)
Writing lessons are offered in elementary schools from grade one to grade VI. Students start learning how to write in grades I and II. Therefore, the process of learning to write at this level is known as early writing lessons, but in grades III, IV, V, and VI it is known as early writing learning. The goal of this study is to find a solution to the problem that low grade students are experiencing with the need to write. The current study includes SDN 112/I Perumnas in grades one and two. Qualitative descriptive is the employed technique. Information that was gathered through surveys, interviews, observations, and documentation In data analysis, quantitative analysis is used. The findings reveal challenges faced by first grade students, including (a) writing letters, words, and simple sentences; (b) writing a follow-up letter; (c) write sentences correctly; (d) can distinguish between the letters b and d (often confused); (e) find it difficult to imitate or copy the written form given by the teacher; and (f) find it difficult to arrange words into simple sentences. In contrast, the two students in the class came together to discuss the topic of (a) letters, words, and a short-term calendar.